Pre- and post-diagnostic beta-blocker use and prognosis after colorectal cancer: results from a population-based study - Jansen, Lina; Weberpals, Janick; Hoffmeister, Michael; Brenner, Hermann (International journal of cancer, 2017)
Recent experimental and epidemiological studies have suggested that beta-blocker use might be associated with better cancer prognosis, but results were inconclusive and only few studies have investigated the association specifically for colorectal cancer (CRC) patients. We investigated this hypothesis using a linked dataset of the Eindhoven area of the Netherlands Cancer Registry and the PHARMO record linkage, including patients diagnosed with CRC between 1998 and 2011. Eligible patients were matched on propensity scores to control for potential confounders such as socio-demographic factors, comorbidity, cancer treatment and use of other medications. Controls were subsequently restricted to active comparators. The association between pre-diagnostic and time-dependent post-diagnostic beta-blocker use and overall survival was estimated using Cox proportional hazard regression models. Subgroup analyses by cancer site and stage and by beta-blocker type were conducted. Of 8,100 CRC patients with a median follow-up of 6.6 years, 1,813 (22%) used beta-blockers prior to diagnosis. In multivariate analysis, we observed no significant association in overall mortality for pre-diagnostic [hazard ratio 1.07, 95% confidence interval (0.96-1.19)] and post-diagnostic [1.10 (0.98-1.23)] beta-blocker use, respectively. Analyses by beta-blocker type, by cancer site, cancer stage and by cumulative dose showed no significant survival improvements for beta-blocker users. However, there was a significant association between cumulative duration of use of 1-12 months and increased overall mortality [1.20 (1.03-1.39)]. Thus, our results do not support the hypothesis of a beneficial effect of pre- or post-diagnostic beta-blocker intake on CRC prognosis, neither for specific patient subgroups nor for specific types of beta-blockers.